Analisis Wacana Plesetan Pada Merk Obat-obatan - Anggara, Siska Novia; Saputri, Ulin Intan; Dewitasari, Intan (Prosiding University Research Colloquium, 2019)
This study aims to determine the play discourse analysis on drug brands. The play language is considered a deviation from the language that is used by the community because it has unusual patterns and violates language conventions. Unlawfulness has two possible assumptions, namely as commendable or as a disgraceful thing. The play language in many speech situations emphasizes humor and humor, and is relaxed. The method used in this research is qualitative method. Qualitative methods as a research procedure in which the descriptive data is in the form of a series of words in writing or verbally from someone and behavior that can be observed. The application of this qualitative method has descriptive properties which mean the data that has been generated in the form of a series of words in a form of quotation. The results of this study indicate that in a play on the boat-drug brand has several different meanings or meanings for the readers.